Effect of family resilience on subjective well-being in patients with advanced cancer: the chain mediating role of perceived social support and psychological resilience - Yang, Yating; He, Fei; Li, Dongfang; Zhao, Yuanyuan; Wang, Ya; Zhang, Haoran; Qiao, Chan; Cui, Yingfang; Lin, Leyun; Guan, Hao (Frontiers in Psychology, 2024)
Purposes: Domestic and international research has found that patients with advanced cancer prioritize increasing their quality of life above extending their lives with simple or intensive treatments. The current study investigates the pathways to improve patients' sense of well-being from the family, social, and individual levels, that is to say, it investigates the mediating roles of comprehending social support as well as psychological resilience in the relationship between family resilience and subjective well-being, and it also provides references for future intervention. Method: The Family Resilience Questionnaire (FRQ), General Well-being Schedule (GWB), Perceived Social Support Scale (PSSS), and the Chinese version of the Cornor-Davidson Resilience Scale 10-item (CD-RISC) were all completed by 338 patients with advanced cancer who took part in the study.Results: The study's findings demonstrated a significant and positive correlation between ２ family resilience, subjective well-being, perceived social support, and psychological resilience. Additionally, there was a significant direct effect of family resilience on subjective well-being as well as a mediating and chain mediating effect between perceived social support and psychological resilience. The findings of this study will be very helpful in the future when it comes to enhancing the quality of life for patients with advanced cancer through intervention.Conclusion: Subjective well-being can be influenced directly by the family resilience of advanced cancer patients, or indirectly through the psychological resilience and perceived social support.